Model Pembelajaran Klasifikasi Fungi Berbasis Proyek Tertintegrasi R-STEM untuk Mengembangkan Sikap Religi dan Ilmiah Siswa MAN Insan Cendikia Jambi - Aty Mulyani (PendIPA Journal of Science Education, 2020)
The main objectives in learning science are (1) aspects of mastery of concepts related to cognitive learning outcomes, (2) aspects of scientific work skills; and (3) aspects of religious and scientific attitudes. At this time the aspect of developing scientific attitudes is not yet an important part of science teachers at this time, so students in the aspects of religious and scientific attitudes are still low, meaning the results of learning cognitive aspects and good skills, but have not been able to develop a religious attitude on God's greatness over his creation or scientific attitude related to curiosity and independence. This research will apply the R-STEM Integrated Project Based Fungi classification model for the development of religious attitudes and scientific attitudes of class X MIA 2 students at MAN Insan Cendekia Jambi with a total of 25 students. This research is a classroom action research with learning stages with integrated project-based R-STEM learning model with the topic of making Tape with local Fungi. In this study, as long as students undertake the tape-making project, data retrieval is carried out related to students' religious attitudes and scientific attitudes. Research data obtained using observation instruments, interviews, and questionnaires. The results of observational data obtained were analyzed descriptively qualitatively; and scoring religious and scientific attitudes using established assessment rubrics. The results of the research and discussion can be concluded that the integrated project-based learning function R-STEM classification is able to develop a religious attitude of God's greatness over his creation, curiosity, and attitudes of student independence; thus the learning model that has been developed is effective.